Mobile-Aided PjBL for Improving Junior High School Students’ Critical Thinking and Learning Motivation - Yulianti, Erni; Husna, Ihda Maf'ulatul; Fitriyah, Isnanik Juni; Nugraheni, Dian; Hamimi, Erti (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Project-Based Learning (PjBL) is often proposed as a way to engage students through authentic tasks, yet classroom observations in junior high schools in Malang indicated that students’ critical thinking and learning motivation were still relatively low. This study examined whether PjBL supported by a mobile application could improve seventh-grade students’ critical thinking and learning motivation on the topic of substances and their changes. A quasi-experimental design was used with 62 students from one junior high school (30 in the experimental group and 32 in the control group). The intervention combined PjBL with a mobile application and supporting materials (modules and student worksheets). Expert review showed that the learning media met acceptable validity criteria, with an average score above 83 percent (high validity). The instruments demonstrated good internal consistency, with Cronbach’s alpha of 0.853 for the critical thinking test and 0.929 for the learning motivation questionnaire. Independent-samples t-tests indicated statistically significant differences between groups (p < 0.05). The experimental group scored higher than the control group in critical thinking (t(60) = 2.33, p = 0.023, d = 1.02) and learning motivation (t(60) = 11.83, p < 0.001, d = 1.13). These results suggest that, in this context, mobile-aided PjBL was associated with higher critical thinking and learning motivation than conventional instruction, and it may be considered for teaching substances and their changes.